ATRIBUTOS FÍSICOS DO SOLO EM DIFERENTES SISTEMAS DE PRODUÇÃO NO MUNICIPIO DE JÓIA/RS - VALENTINI, ANA P. F.; ABREU, FERNANDO; GROSSMANN, GILBERTO; MANCHINI, TIAGO; BERTO, JORGE; FERNANDES, SANDRA; QUADROS, VALMIR D. (Salão do Conhecimento, 2013)
Resumo